Naturally Occurring Xanthones; Biological Activities, Chemical Profiles and In Silico Drug Discovery - El-Seedi, Hesham R.; Ibrahim, Hasnaa M.S.; Yosri, Nermeen; Ibrahim, Mahmoud A.A.; Hegazy, Mohamed-Elamir F.; Setzer, William N.; Guo, Zhiming; Zou, Xiaobo; Refaey, Mohamed S.; Salem, Suhila E.; Musharraf, Syed G.; Saeed, Aamer; et al. (Current Medicinal Chemistry, 2024)
Xanthones are widely distributed polyphenols, present commonly in higher plants; Garcinia, Calophyllum, Hypericum, Platonia, Mangifera, Gentiana and Swertia. Xanthone tricyclic scaffold is able to interact with different biological targets, showing antibacterial and cytotoxic effects, as well as potent effects against osteoarthritis, malaria, and cardiovascular diseases. Thus, in this article we focused on pharmacological effects, applications and preclinical studies with the recent updates of xanthon´s isolated compounds from 2017-2020. We found that only α-mangostin, gambogic acid, and mangiferin, have been subjected to preclinical studies with particular emphasis on the development of anticancer, diabetes, antimicrobial and hepatoprotective therapeutics. Molecular docking calculations were performed to predict the binding affinities of xanthone-derived compounds against SARS-CoV-2 Mpro. According to the results, cratoxanthone E and morellic acid demonstrated promising binding affinities towards SARS-CoV-2 Mpro with docking scores of −11.2 and −11.0 kcal/mol, respectively. Binding features manifested the capability of cratoxanthone E and morellic acid to exhibit nine and five hydrogen bonds, respectively, with the key amino acids of the Mpro active site. In conclusion, cratoxanthone E and morellic acid are promising anti-COVID-19 drug candidates that warrant further detailed in vivo experimental estimation and clinical assessment.
Keywords: phase II clinical trial